1992
DOI: 10.1042/bj2840161
|View full text |Cite
|
Sign up to set email alerts
|

Affinity purification of the hepatic high-density lipoprotein receptor identifies two acidic glycoproteins and enables further characterization of their binding properties

Abstract: Several high-density lipoprotein (HDL)-binding proteins, candidates for the putative HDL receptor, have recently been identified, including two membrane proteins: HB1 of 120 kDa and HB2 of 100 kDa, present in rat and human liver plasma membranes respectively. Further insights into their function however, have been hampered by poor recoveries of these hydrophobic peptides, and the present work was undertaken to improve yields and enable a more detailed investigation of their properties. A significant improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 36 publications
2
25
1
Order By: Relevance
“…However, the intimal distributions of oxidized HDL particles and oxidized LDL particles were somewhat distinct compared with the data of Itabe et al 27 120 kDa in human placenta 28 and 120 kDa or 100 kDa in rat and human liver plasma membranes. 21 Recently, it was reported that the class B scavenger receptor SR-BI, another native HDL receptor, had an amino acid sequence homology of about 30% to CD36 and a molecular mass of about 82 kDa. 9 Native HDL binding proteins found in the liver or peripheral tissues therefore appear to have distinct structures and different roles.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intimal distributions of oxidized HDL particles and oxidized LDL particles were somewhat distinct compared with the data of Itabe et al 27 120 kDa in human placenta 28 and 120 kDa or 100 kDa in rat and human liver plasma membranes. 21 Recently, it was reported that the class B scavenger receptor SR-BI, another native HDL receptor, had an amino acid sequence homology of about 30% to CD36 and a molecular mass of about 82 kDa. 9 Native HDL binding proteins found in the liver or peripheral tissues therefore appear to have distinct structures and different roles.…”
Section: Discussionmentioning
confidence: 99%
“…Protein Sequencing-HB 2 , a glycoprotein of M r 100,000 was purified from rat liver plasma membrane as described previously (12). Attempts at NH 2 -terminal sequencing were unsuccessful.…”
Section: Methodsmentioning
confidence: 99%
“…We have identified two liver plasma membrane proteins named HB 1 and HB 2 (HDL-binding proteins 1 and 2) which are candidate HDL receptors (8,12). Although present in low abundance, HB 2 was purified in sufficient quantities to provide amino acid sequence data.…”
mentioning
confidence: 99%
“…Identification of the basic residues of the m27-mer, within the GAG-binding consensus sequence (A) and outside the GAG-binding consensus sequence (B), which are important for heparin binding. Nine synthetic peptides were applied to heparinSepharose 4B, the m27-mer, R83A, H84A, R86A, R83A/H84A/R86A (triple mutant), K89A, R95A, Lys-102 Ϫ (mouse apoSAA2 [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] ) which lacked the carboxyl-terminal Lys-102, and the h27-mer (human apoSAA2 78 -104 ). The elution profile of the Lys-102 Ϫ peptide on heparin/ Affi-Gel is also shown.…”
Section: Figmentioning
confidence: 99%